What does the French REIN registry tell us about Stage 4-5 CKD care in older adults? - Moranne, Olivier; Hamroun, Aghilès; Couchoud, Cécile (Frontiers in Nephrology, 2023)
The aim of this paper is to illustrate all the clinical epidemiology searches made within the REIN to improve CKD stage 4-5 care in the elderly. We summarize various studies describing clinical practice, care organization, prognosis and health economics evaluation in order to develop personalized care plans and decision-making tools. In France, for 20 years now, various databases have been mobilized including the national REIN registry which includes all patients receiving dialysis or transplantation. REIN data are indirectly linked to the French administrative healthcare database. They are also pooled with data from the PSPA cohort, a multicenter prospective cohort study of patients aged 75 or over with advanced CKD, monitored for 5 years, and the CKD-REIN clinical-based prospective cohort which included 3033 patients with CKD stage 3-4 from 2013 to 2016. During our various research work, we identified heterogeneous trajectories specific to this growing elderly population, raising ethical, organizational and economic issues. Renal registries will help clinicians, health providers and policy-makers if suitable decision- making tools are developed and validated.